Comparative analysis of third-generation dual-energy CT and IVUS for in-stent restenosis detection - Mohey E. A. Eldeeb; Mohamed A. Mostafa; Tarek A. Nagiub; Mohammed H. E. Alshair; Islam E. Shehata (BMC Cardiovascular Disorders)
Abstract Purpose Prior studies have assessed in-stent diameter restenosis (ISDR) in coronary arteries using 64-slice multidetector computed tomography coronary angiography (MDCT-CA) compared to invasive coronary angiography (ICA), which is the gold standard. This study aimed to compare the diagnostic accuracy of monoenergetic reconstruction using third-generation dual-source dual-energy CT (DSDECT) to that of ICA reconstruction via adjunctive intravascular ultrasonography (IVUS) for evaluating the ISDR. Methods A total of 95 patients with previously stented coronary arteries (involving 110 stents) underwent DSDECT followed by ICA and IVUS within a 24-h timeframe. The specificities, sensitivities, negative predictive values (NPVs), and positive predictive values (PPVs) of the DSDECT and ICA were compared for confirming or excluding the ISDR using in-stent area restenosis (ISAR) and a minimal luminal area (MLA) ≤ 4.0 mm2 on IVUS as the reference standard. Results Compared with IVUS, the latest DSDECT demonstrated good sensitivity (100%), specificity (92.4%), and accuracy (96.1%) in detecting the ISDR. Our study highlights a limitation in assessability for stents with diameters < 3 mm, emphasizing the importance of careful patient selection. When employing an IVUS MLA of 4.0 mm2 as a reference for identifying the ISDR, no significant difference was observed between DSDECT and ICA in the identification of the ISDR. However, it is important to note that the use of absolute cut-offs, such as < 6.0 mm2 in the left main or < 4.0 mm2, may not universally apply across varying ethnicities and between sexes. The interpretation of the minimal luminal area (MLA) should be considered in the context of individual patient characteristics, and caution is advised to avoid potential misleading conclusions based solely on absolute thresholds. Conclusion In summary, when assessing stent patency, the latest DSDECT exhibits similar performance to coronary angiography and IVUS. Moreover, it offers noninvasiveness, cost-effectiveness, and ease of operation, which are advantageous characteristics. However, it is essential to consider limitations in patient eligibility, including factors such as prior cardiac devices, arrhythmias, and any degree of chronic renal insufficiency, which may impact CT imaging analysis. The 100% negative predictive value (NPV) of third-generation DSDECT reliably excludes in-stent restenosis (ISDR), potentially obviating invasive angiography in stable patients with patent stents. Trial registration ZU-IRB#3915/13-8-2017 Registered 13 August 2017, email: IRB_123@medicine.zu.edu.eg.